Effect of tillage deep and phosphate fertilizer in growth and yield of sun flower (Helianthusannuus L.) - Mahdie, Ali Salah (Journal of Kerbala for Agricultural Sciences, 2013)
An experiment was carried out during the 2001 and 2002 growing seasons at Akad horticulture station , Shatra , Theqar governorate .This study was conducted to investigate the influence of plowing depth and phosphorous fertilization on growth and yield , its components , oil percentage and oil yield of sunflower for variety Peredovick. Also there interactions . Split plots arrangement in (R.C.B.D) with four replicates was used. The main treatment was the plowing depth (0-20) cm and (0-40) cm, where as the fertilizer levels of phosphor (0, 80 and 160) kg p2o5/ha was used as sub treatment. The area of experiment unite was (3*3) m contained (4) rows, planting at (75*30) cm space. Results showed that plowing depth (0-40) cm gave higher values for most characteristics during y the two study seasons 2001 and 2002 respectively. Results olso showed that deep plowing (0-40)cm gave a higher yield of seed (2.246 , 2.351) ton / ha , higher oil percentage 40.9 % and 41.1 % and oil yield ( 0.928 , 0.973) ton / ha during for two study seasons 2001 and 2002. The fertilizer levels of (160) kg P2O5 /ha gave higher yield of seed ( 2.372 , 2.064) ton / ha ,oil percentage 42.2 % , 42.0 % and oil yield (1.006 , 1.032) ton/ha for two study seasons 2001 and 2002. Therefore the best combination was deep plowing (0-40) cm with 160 kg/ha P2O5 increased the yield of seed which was (2.610 , 2.682) ton/ha and oil percentage 44.6 % , 44.9% also increased the yield of oil which was (1.138 and 1.183) ton/ha for 2001 and 2002 respectively.